PARADIGM AND RATIONALITY: CRITICAL REVIEW OF THE THOUGHTS OF THOMAS KUHN AND IBNU RUSYD - Lalu Ibnurusd Al Hafied (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This article critically examines the thoughts of Thomas Kuhn and Ibn Rushd in order to understand the epistemological structure and dynamics of science, by highlighting two fundamental concepts: paradigm and rationality. Thomas Kuhn, through his theory of scientific revolutions , argued that the development of science does not occur linearly and cumulatively, but rather through paradigm leaps triggered by internal crises in the scientific community and resolved through collective consensus. On the other hand, Ibn Rushd, as a representative of rationalist philosophers in the classical Islamic thought treasury, places reason and logic as universal epistemic foundations in revealing scientific truth, and firmly rejects the dominance of theological authority that hinders freedom of thought. This study reveals that although both come from different traditions and historical contexts, there is a common ground in the critical attitude towards intellectual stagnation and the drive to open up space for renewal of thought. However, epistemologically, both show sharp divergences: Kuhn is based on contextual paradigmatic relativism, while Ibn Rushd is rooted in transhistorical rational objectivism. Using a comparative-philosophical approach, this article concludes that a critical synthesis of the two views can enrich contemporary discourse on the foundations and direction of the development of science.